Empowering agriculture with renewable energy for sustainable irrigation and inclusive policies - Rauniyar, Amrita; Mishra, Anuj; Shrestha, Shisher (International Water Management Institute, 2025)
The workshop under Science-Policy Dialogue on Solar Irrigation in Nepal brought together policymakers, researchers, development partners, civil society, and private sector representatives aimed at fostering inclusive and sustainable solar irrigation programs. Organized under the SoLAR project in collaboration with the Alternative Energy Promotion Centre (AEPC), the dialogue served as a platform to share evidence, discuss policy frameworks, and explore pathways to scale solar irrigation initiatives in Nepal.